Oligodendrocyte and Interneuron Density in Hippocampal Subfields in Schizophrenia and Association of Oligodendrocyte Number with Cognitive Deficits - Falkai, Peter; Steiner, Johann; Malchow, Berend; Shariati, Jawid; Knaus, Andreas; Bernstein, Hans-Gert; Schneider-Axmann, Thomas; Kraus, Theo; Hasan, Alkomiet; Bogerts, Bernhard; Schmitt, Andrea (Frontiers in Cellular Neuroscience, 2016)
In schizophrenia, previous stereological post-mortem investigations of anterior, posterior, and total hippocampal subfields showed no alterations in total neuron number but did show decreased oligodendrocyte numbers in CA4, an area that corresponds to the polymorph layer of the dentate gyrus. However, these investigations identified oligodendrocytes only on the basis of morphological criteria in Nissl staining and did not assess alterations of interneurons with immunohistochemical markers. Moreover, the association of findings in the posterior hippocampus with cognitive deficits remains unknown. On the basis of the available clinical records, we compared patients with definite and possible cognitive dysfunction; nine patients had evidence in their records of either definite (n=4) or possible (n=5) cognitive dysfunction. Additionally, we assessed the density of two oligodendrocyte subpopulations immunostained by the oligodendrocyte transcription factors Olig1 and Olig2 and of interneurons immunolabeled by parvalbumin. We investigated posterior hippocampal subregions in the post-mortem brains of the same schizophrenia patients (n=10) and healthy controls (n=10) we examined in our previously published stereological studies. Our stereological studies found that patients with definite cognitive deficits had decreased total / Nissl-stained oligodendrocyte numbers in the left (p=0.014) and right (p=0.050) CA4, left CA2/3 (p=0.050), left CA1 (p=0.027), and left (p=0.050) and right (p=0.014) subiculum of the anterior part of the hippocampus compared to patients with possible cognitive deficits. In the present study, we found no significant influence of definite cognitive deficits in the posterior part of the hippocampus, whereas in the entire hippocampus schizophrenia patients with definite cognitive deficits showed decreased oligodendrocyte numbers in the left (p=0.050) and right (p=0.050) dentate gyrus and left CA2/3 (p=0.050). We did not find significant differences in Olig1-, Olig2-, or parvalbumin-positive cell density between schizophrenia patients and controls in any of the subregions of the posterior hippocampus. Based on the results from our stereological study we hypothesize that a decreased number of oligodendrocytes in the anterior and entire hippocampus may be involved in cognitive deficits by impairing the connectivity of this structure in schizophrenia. In the posterior hippocampus, we could not replicate previously reported findings of decreased interneurons from the entire hippocampus.